Microbial biotechnology in agro-environmental sustainability - Singh, Jay Shankar; Singh, D. P., 1960- (New and future developments in microbial biotechnology and bioengineering., 2019)
New and Future Developments in Microbial Biotechnology and Bioengineering: Microbial Biotechnology in Agro-environmental Sustainability describes, in detail, the various roles of microbial resources in the management of crop diseases and how microbes can be used as a source of income for biomass and bioenergy production. In addition, the book covers microbial inoculants as bio-fertilizers to enhance crop productivity, along with degraded land restoration. Users will find the latest information in the field of microbial biotechnology and its further applications in bio-fertilizers, bio-pesticides, its generation as an alternative source of energy, restoration degraded and marginal lands, the mitigation of global warming gases, and more.